Community Multiculturalism in Pematangsiantar City: Ethnicity, Religion and Culture - Siburian, Eric Sapetra; Sinurat, Anggiat; Haloho, Bongguk (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Pematangsiantar City as one of the cities in Indonesia with a multicultural society. Pematangsiantar City is a stopover city located in the middle of Simalungun district which has a cultural slogan